Development and Evaluation of Antifungal in vivoof Liposomal Amphotericin B - Nguyen, Thanh Hai (2016)
Amphotericin B is a polyene antifungal drug used intravenously for systemic fungal infections. It has severe and potentially lethal side effects, therefore, it has been limited use in clinical. Liposomes are widely used as vehicles to target organ in pharmaceutical technology due to their ability to improve the delivery of drugs, increasing therapeutic efficacy and decreasing toxicity. The aim of this study is to prepare a liposomal amphotericin B by hydration of a thin lipid film and ethanol-injection methods and evaluate its antifungal activity in vivo. Prepared liposomal amphotericin B by both methods has particle size smaller than 150 nm, quite homogeneous and the entrapment drug was greater than 90%. The antifungal activity of liposomal amphotericin B was studied on three strains Candida albicans, Cryptococcus neoformans andAspergillus fumigatus fungal infection in mice models. Our results have shown that liposomal amphotericin B prepared by both methods have strong effect to prolong the survival in the infected mice and significantly reduced the Colony Forming Units (CFU) in target organ with similar effect of AmBisome